Foreign direct investment in the Republic of Kazakhstan: trends and prospects. (Journal of Economic Research & Business Administration, 2016)
The functioning of the economic complex of the country is impossible without investment, ensuring the continuity of reproduction, development and implementation of industrial, innovative and social programs and projects in order to increase production, to increase efficiency of economic development of the state. For the development of international economic cooperation it is necessary to choose the optimal form of attraction and use of additional funds from abroad, the policy framework for the functioning of foreign investments on the territory of the Republic of Kazakhstan. Key problem of investment policy is formation of favorable investment climate. An important source of foreign investments are keenly sought after countries of the near abroad. Therefore, in order to attract potential investors to the Kazakh market, you must first reduce taxes and you need to enter the stimulating benefits on investment in the manufacturing sector.
Keywords: foreign direct investment in the Republic of Kazakhstan; the key problem of investment policy; investment climate.